2017
DOI: 10.1158/1078-0432.ccr-16-2821
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Intratumoral Injection ofCCL21Gene–Modified Dendritic Cells in Lung Cancer Elicits Tumor-Specific Immune Responses and CD8+ T-cell Infiltration

Abstract: Purpose A phase I study was conducted to determine safety, clinical efficacy, and anti-tumor immune responses in patients with advanced non-small cell lung carcinoma (NSCLC) following intratumoral (IT) administration of autologous dendritic cells (DC) transduced with an adenoviral (Ad) vector expressing the CCL21 gene (Ad-CCL21-DC). We evaluated safety and tumor antigen-specific immune responses following in situ vaccination (ClinicalTrials.gov: NCT01574222). Experimental Design Sixteen stage IIIB/IV NSCLC s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
134
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(142 citation statements)
references
References 49 publications
1
134
0
Order By: Relevance
“…Recently, a phase I trial of patients with advanced NSCLC suggested that intratumoral vaccination with autologous DCs could increase infiltration of CD8+ T cells into tumors and increase the expression levels of PD-L1 [34].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a phase I trial of patients with advanced NSCLC suggested that intratumoral vaccination with autologous DCs could increase infiltration of CD8+ T cells into tumors and increase the expression levels of PD-L1 [34].…”
Section: Discussionmentioning
confidence: 99%
“…133 However, these cells are rare and transcriptomic analysis of lung cancers and peritumoral tissues from mice demonstrate that the majority of infiltrating myeloid cells are actually CD11b + DCs. 135 Recently in mice, Figure 3. 130,131 The importance of DCs in lung cancer is demonstrated by ongoing efforts to harness these cells for therapeutic purposes.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…134 In a more recent phase I trial, NSCLC patients receiving autologous genetically modified DCs (overexpressing lymphoid-tissue organizing chemokine CCL21) had better anti-tumour immunity, CD8 T-cell infiltration and increased tumour PD-L1 expression. 135 Recently in mice, Figure 3. Dendritic cells (DCs) are professional antigen-presenting cells that sample and present antigen to T cells within the lamina propria and associated lymph nodes.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Recent clinical trials showed the efficacy of in situ DC vaccination in achieving clinical and immunological responses. In a clinical study, where CCL21 transduced DCs were used in non-small cell lung carcinomas, a significant increase in CD8+ T cell infiltration was detected in 56% of patients and it was associated with PD-L1 up-regulation [65]. Moreover, intratumoral injection of activated DCs in patients with different neoplasms enhanced lymphocyte infiltration and specific cytokine production by DCs, which correlated with stable disease and prolonged survival [66].…”
Section: In Situ Vaccinationmentioning
confidence: 99%